Indicadores de desempenho financeiro das capitais do Nordeste: uma aplicação de análise multicritério - Silva, Débora Oliveira da (2019)
The Municipality plays a prominent role in the governmental action, because it is in this space that things happen. Besides being a central figure in the execution of public policies, it represents an important object of evaluation of the Brazilian scenario in terms of public sector financing and expenditures. In this context, this study presents financial indicators, extracted from financial statements that show the situation of revenue, expenditure, indebtedness, liquidity and capacity to generate savings, with the objective of analyzing the financial performance of the capital cities of the Northeast in the year 2018. To the methodological aspects, the research is classified, as far as the objectives, as exploratory-descriptive, as to the methods, documentary, and as to the quantitative approach, with data collection performed through the National Treasury Secretariat (STN) website. The results show that there is a structural problem in relation to the commitment of the budget with compulsory expenditures, the level of investment is low, the Restos to Pay mode is the main source of financing and that São Luís, unlike the other municipalities studied, presents the highest level of indebtedness. Finally, with the application of multicriteria analysis through the PROMETHEE technique, it was possible to identify performance rankings and to compare, in a global and by category, the performance of the cities surveyed.